Antimicrobial ointment based on Bacillus subtilis subsp. subtilis HSFI-9 isolated from Sea Cucumber of Kodek Bay Lombok Indonesia - Rakhmawatie, Maya Dian; Diatri, Devita; Samiroh, Samiroh; Abdillah, Rifqi; Arfiyanti, Mega Pandu; Ethica, Stalis Norma; Zilda, Dewi Seswita (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2025)
The ethyl acetate extract of Bacillus subtilis subsp. subtilis HSFI-9, a bacteria isolated from intestinal fermentation of sea cucumbers (Holothuria scabra) is known to have antimicrobial properties. This research aimed to determine the activity of HSFI-9 extract ointment against Staphylococcus aureus and Candida albicans. Extract ointment is a topical preparation for skin infections made from a mixture of Vaseline Alba and Adeps lanae bases. The extract ointment was prepared into four concentrations of 0.003%, 0.03%, 0.3%, and 1% w/v using HSFI-9 as active ingredient. Antimicrobial assay was carried out in vitro using the disc diffusion method. The extract ointment was evaluated based on organoleptic, homogeneity, spreadability, adhesion characteristics, and pH tests. The optimal concentration of the extract ointment to inhibit the growth of S. aureus 0.3% (inhibition zone of 11.67±1.26 mm) and against C. albicans is 0.03% (inhibition zone of 10.16±1.50 mm). The activity of the extract ointment was categorized as strong although not as strong as the antibiotic control ointment Mupirocin 2% or Ketoconazole 2%. The extract ointment organoleptic indicated a characteristic odor of ethyl acetate, was yellowish-white ointment, and had a homogeneous and smooth consistency. The extract ointment also had properties such as good spreadability but poor adhesion and tended to have an acidic pH ( 4.5). The HSFI-9 extract can be declared feasible for the development of topical antimicrobials. The ointment still needs to be optimized, especially regarding improving the adhesion characteristic and pH to be safe for the skin and mucosa.